Ananas comosus 'Variegatus' Variegated Pineapple - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document provides an overview of the variegated pineapple (Ananas comosus ‘Variegatus’), detailing its characteristics, planting requirements, and uses. The plant features stiff, bright green leaves with spiny tips and margins, and produces fruit on a central stalk. It is a perennial herbaceous plant suitable for USDA hardiness zones 10 through 11. The variegated pineapple is valued for its ornamental appeal, particularly its striking variegated foliage. It can be used as ground cover, an accent, or in mass plantings. The document also highlights the plant’s growth conditions, pest resistance, and propagation methods. Original publication date October 1999.